Benchmarking alfalfa water use efficiency and quantifying yield gaps in the U.S. central Great Plains - Fink, Kaylin Paige (Kansas State University, 2021)
With an annual production of 116 MMt, the U.S. accounts for 21% of the global alfalfa production. Still, a benchmark for alfalfa water use efficiency (WUE, kg aboveground dry matter per mm water supply) is unavailable, the magnitude of alfalfa yield gaps (YG) remains unknown, and information about management practices to close the yield gap are scarce. Thus, our objectives were to i) benchmark alfalfa WUE, ii) quantify YG in commercial alfalfa fields, iii) characterize current crop management practices adopted by alfalfa producers, and iv) identify management opportunities to improve alfalfa yield, WUE, and reduce YG using a data-rich approach. We conducted a systematic review of the scientific literature that resulted in a final database containing alfalfa forage yield and growing season evapotranspiration (ETa) for 195 treatment means across 24 manuscripts. The dataset was then used to fit a boundary function that resulted in a benchmark WUE of 33 kg ha⁻¹ mm⁻¹. We then collected field-level management information and associated weather, soil, and yield (Ya) data from 394 commercial rainfed alfalfa fields over four harvest years (2016-2019) by interviewing alfalfa growers in Kansas, which accounts for 5% of U.S. alfalfa production, for an assessment of on-farm yield, WUE, and YG. Actual yields in our dataset ranged from 0.9 to 22.4 Mg ha⁻¹, averaging 8.9 Mg ha⁻¹. Average YG against the benchmark WUE was 57% of the water-limited yield (Yw). Conditional inference tree analyses show limited room for improvement of alfalfa yields and WUE through management, as only row spacing, and phosphorus applications were significant managerial factors. To our knowledge, this is the first study in alfalfa WUE benchmark with detailed on-farm assessment of the alfalfa yield-limiting factors, which can serve as a guideline for future studies evaluating WUE and the YG in perennial crops. Our work originated the question of whether there are fewer opportunities to reduce YG of perennial crops through management as compared to annual crops, which could be the focus of future research.
Keywords: Alfalfa; Yield gap; Kansas; Water use efficiency